A study on handling of stranded motorcycles in Malaysia - Sulaiman, S.A. (Springer Singapore, 2019)
In Malaysia, motorcycles are well known as vehicles with significantly low fuel consumption due to its low weight. Nevertheless, motorcycles also contribute to many issues such as emission, noise, traffic, and a few others. On top of that, motorcycle riders are exposed to various situations such as exposure to harsh weather, tendency of being hit by larger vehicles, and unexpected breakdown. This chapter discusses a study on the handling of motorcycles in the event when they are stranded. The primary concern here is on the safety of the riders and other road users. Although this chapter is not directly related to energy efficiency, it looks into an important aspect of a transport system that has a significant feature of low fuel consumption. The study was conducted through a survey and also via an interview with the local authority. Â© Springer Nature Singapore Pte Ltd. 2020.